Frailty phenotype and self-reported crashes and driving space: Baseline AAA LongROAD. (December 2019) - Man, Cora; Ng, Linda S.; Molnar, Lisa J.; Eby, David W.; Ryan, Lindsay H.; DiGuiseppi, Carolyn; Strogatz, David; Betz, Marian E.; Hill, Linda; Guralnik, Jack; Crowe, Christopher L.; Li, Guohua; et al.
Abstract: Introduction: The present study uses data from the American Automobile Association (AAA) Longitudinal Research on Aging Drivers (LongROAD) study to assess the association of the frailty phenotype with reduced driving space and involvement in motor vehicle crashes. Methods: The LongROAD study is a multisite prospective cohort study of participants aged 65–79 years. Fried's frailty phenotype status at baseline and self-reported restricted driving space in the past three months and at least one self-reported crash in the recent year are examined. Multivariable logistic regression was used to obtain odds ratios, adjusting for covariates and clustering by site. Results: Pre-frail (i.e. only 1–2 indicators of frailty) participants had 30% higher odds (adjusted OR = 1.3, 95% CI:1.0–1.8) of reporting involvement in a crash in the prior year than non-frail participants after adjusting for sex, age, depression, word recall, average miles driven per week, and site. No association for reduced driving space for frail older drivers was found. Conclusions: The frailty phenotype is associated with motor vehicle crashes, but not reduced driving space. Our findings suggest that future research should be focused on the identification of pre-frail older adult drivers to improve the health and quality of life of older adult drivers. Highlights: The frailty phenotype may be useful in identifying drivers at risk for negative outcomes. Pre-frail drivers were the ones associated with at least one crash compared to non-frail drivers. Interventions for drivers who are starting to become frail may improve quality of life.